Front Cover. Issue 3 (March 2017) - Turbé, Anne; Strubbe, Diederik; Mori, Emiliano; Carrete, Martina; Chiron, François; Clergeau, Philippe; González‐Moreno, Pablo; Le Louarn, Marine; Luna, Alvaro; Menchetti, Mattia; Nentwig, Wolfgang; Pârâu, Liviu G.; et al.
Abstract : The cover image, by Anne Turbé et al ., is based on the Biodiversity Research Assessing the assessments: evaluation of four impact assessment protocols for invasive alien species, DOI:10.1111/ddi.12528 . Photo Credit:Marine Le Louarn.